(untitled) (Contemporary Mathematics, 2024)
This manuscript commits to analyzing the existence and uniqueness of mild solution and trajectory controllability of conformable Hilfer fractional neutral stochastic integro-differential system with infinite delay through Lipschitz, growth conditions and properties of semigroup theory, controllability theory, stochastic analysis techniques, and Banach fixed point theorem with example. This manuscript mainly focuses on fractional system provide the mathematical foundation to understand and control complex, real-world systems with memory, and randomness.